Fecal carriage of carbapenemase and AmpC-β-lactamase producers among extended spectrum β-Lactamase-producing E. coli and Klebsiella spp. isolates in patients attending hospitals - Zakaria Garba; Isidore J. O. Bonkoungou; Namwin Siourimè Somda; Magloire H. Natama; Georges Somé; Lassana Sangaré; Nicolas Barro; Halidou Tinto (BMC Infectious Diseases)
Abstract Background Extended-spectrum β-lactamase-producing Enterobacterales (ESBL-PE), particularly Escherichia coli and Klebsiella pneumoniae, have been consistently associated with treatment failure, high mortality and morbidity. The emergence of carbapenem resistance among ESBL-PE strains exacerbates the antimicrobial resistance. However, data are very limited in developing countries as Burkina Faso. This study aimed to determine the prevalence of carbapenemase and AmpC-β-lactamase production among ESBL-producing E. coli (ESBL-Ec) and Klebsiella spp. (ESBL-K) isolated from patients’ stool in Burkina Faso. Materials and methods From January 2020 to June 2022, we isolated 277 ESBL-PE from patients’ stool in five hospitals in Burkina Faso. The strains were isolated on ESBL-selective chromogenic media and identified using API20E. The isolates were tested against 15 antimicrobial agents using the disc-diffusion method on Mueller–Hinton (MH) agar. ESBL production was confirmed by double disc synergy method. Carbapenemase and AmpC-β-lactamase production and phenotypic co-resistance were determined. Results Among the 277 ESBL-PE strains isolated, 203 were E. coli, and 74 were Klebsiella spp. Of these bacteria, 2.9% were carbapenemase producers and 6.5% were AmpC-β-lactamase producers. The carbapenemase producers were detected at tertiary and secondary hospitals, mainly in hospitalized patients and females, whereas AmpC-β-lactamase producers were detected at all levels of healthcare, predominantly in non-hospitalized patients, male, and under 15 years of age. The co-resistance rates were as high as 82% for fluoroquinolones, 91% for aminoglycosides, and 94% for sulfonamides. Fosfomycin resistance was 2.5% for ESBL-Ec and 50% for ESBL-K. Conclusion This study showed that ESBL-PEs co-produce carbapenemase and/or AmpC-β-lactamase. High co-resistances were reported for commonly used antibiotic agents. Therefore, screening for carbapenem-resistant Enterobacterales (CRE) carriage is necessary to limit its spread within hospitals.